Clinical Characteristics And Outcomes Of Postpartum Hemorrhage In Remote Areas Of Tual City, Maluku, Indonesia, 2024 - David Eriandi Ginting; Marlina Yanti (International Journal of Health Engineering and Technology, 2026)
Postpartum hemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality worldwide. In Indonesia, PPH accounts for approximately 27% of maternal deaths, with a higher burden in remote and resource-limited areas. To describe the clinical characteristics, management, and outcomes of PPH cases in Tual City, Maluku, in 2024. This retrospective descriptive study included all PPH cases managed at RSUD Maren Hi Noho Renuat, the only referral hospital in Tual City, from January to December 2024 (total sampling). Data were extracted from medical records and delivery registers and analyzed descriptively. Most cases occurred among women aged 20–34 years (67%) and multiparous mothers (75%). Half of the women had completed senior high school. Urban mainland residents accounted for 50% of cases, followed by rural (33%) and remote island residents (17%). Deliveries were evenly distributed between health facilities and non-facility settings (50% each), including one case aboard a ferry during referral. Skilled birth attendants assisted 58% of deliveries, while 42% were attended by traditional birth attendants. Retained placenta was the most frequent cause of PPH (84%). All patients received uterotonics; 67% required blood transfusion and 25% underwent surgical interventions (17% curettage, 8% hysterectomy). Maternal outcomes were favorable, with 92% full recovery, 8% near-miss events, and no maternal deaths. Neonatal outcomes were excellent, with 100% live births and no  neonatal mortality. Retained placenta was the leading cause of PPH in Tual. Improving institutional delivery coverage, strengthening referral systems, and enhancing community education are crucial to reduce preventable maternal morbidity in remote island settings.